Thank you for the opportunity to help you with your question! IF you have any clarification, please don't hesitate to ask and I will do my best to answer.
++++++++++++

y = 1 – x

y = x – 5

y = x – 5 => -1(y = x – 5)
=> -y = -x + 5 => -y = 5 – x

Therefore,

y = 1 – x

-y = 5 – x

0 = 6 – 2x => 0 + 2x = 6 =>
2x = 6 => x = 6/2

Therefore, x = 3

Proof:

y = 1 – x

substitute for x

y = 1 – 3

y = -2

y = x – 5

substitute for x

y = 3 – 5

y = -2

Please let me know if you need any clarification. I'm always happy to answer your questions.

Sep 13th, 2015

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.